Energy analysis of a 10 kW-class power-to-gas system based on a solid oxide electrolyzer (SOE). (1st November 2019) - Kupecki, Jakub; Motylinski, Konrad; Jagielski, Stanisław; Wierzbicki, Michal; Brouwer, Jack; Naumovich, Yevgeniy; Skrzypkiewicz, Marek
Graphical abstract: Highlights: Model of a 10 kW-class P2G system was developed. Experimental data were collected during single cell testing. System-level simulator was used to determine electrical efficiency. Three temperature levels (700, 750 and 800 °C) were considered in the analysis. Abstract: This article presents a conceptual power-to-gas system based on a high temperature electrolysis unit. The solid oxide electrolyzer (SOE) delivers highly efficient conversion of intermittent electricity from wind and solar into hydrogen, which can then be directly injected into the gas grid or used to synthesize methane in a Sabatier reactor. Due to the unpredictable character of these sources, the grid experiences imbalances, which destabilize the energy system. The solution, in the form of a high temperature electrolyzer, mitigates the problem by coupling the electric and gas grids. The advantages of solid oxide electrolysis over conventional electrolyzers are as follows: (i) SOEC offers outstanding efficiency, exceeding 70–80%, (ii) no noble metals are needed for catalytic reactions – the ceramic materials of electrodes and the high temperature substitute noble metal loading, (iii) SOEC mode can be switched to SOFC and the interchange supports the unique self-healing of the cells, (iv) modular design makes it easy to scale up the system based on the SOEC stack, (v) absence of any liquid electrolyte that has to be replaced on a regular basis. The 10 kW-class power-to-gas system is presented and the efficiency of the system assessed and discussed from an energy point of view. Accepting the current assumptions related to the performance of cells making up the electrolysis unit, the system can achieve efficiency in excess of 74%. The modeling approach is given and the performance map of the system is analyzed with respect to the variation of voltage and steam utilization in the electrolyzer.